Erythropoietin and Friedreich Ataxia: Time for a Reappraisal? - Boesch, Sylvia; Indelicato, Elisabetta (Frontiers in Neuroscience, 2019)
Friedreich ataxia (FRDA) is a rare neurological disorder due to deficiency of the mitochondrial protein frataxin. Frataxin deficiency results in impaired mitochondrial function and iron deposition in affected tissues. Erythropoietin (EPO) is a cytokine which was mostly known as a key regulator of erythropoiesis until cumulative evidence showed additional neurotrophic and neuroprotective properties. These features offered the rationale for advancement of EPO in clinical trials in different neurological disorders in the past years, including FRDA. Several mechanisms of action of EPO may be beneficial in FRDA. First of all, EPO exposure results in frataxin upregulation in vitro and in vivo. By promoting erythropoiesis, EPO influences iron metabolism and induces shifts in iron pool which may ameliorate conditions of free iron excess and iron accumulation. Furthermore, EPO signaling is crucial for mitochondrial gene activation and mitochondrial biogenesis. Up to date nine clinical trials investigated the effects of EPO and derivatives in FRDA. The majority of these studies had a proof-of-concept design. Considering the natural history of FRDA, all of them were too short in duration and not powered for clinical changes. However, these studies addressed significant issues in the treatment with EPO, such as (1) the challenge of the dose finding, (2) stability of frataxin up-regulation, (3) continuous versus intermittent stimulation with EPO/regimen, or (4) tissue changes in vivo after EPO exposure (muscle biopsy, brain imaging). Despite several clinical trials in the past, no treatment is available for the treatment of FRDA. Current lines of research focus on gene therapy, frataxin replacement strategies and on regulation of key metabolic checkpoints such as NrF2. Due to potential crosstalk with all these mechanisms, interventions on EPO pathway still represent a valuable research field. The recent development of small EPO mimetics which maintain cytoprotective properties without erythropoietic action may open a new era in EPO research for the treatment of FRDA.